Ongoing evolution of Chlamydia trachomatis lymphogranuloma venereum: exploring the genomic diversity of circulating strains - Seth-Smith, Helena M B; Bénard, Angèle; Bruisten, Sylvia M; Versteeg, Bart; Herrmann, Björn; Kok, Jen; Carter, Ian; Peuchant, Olivia; Bébéar, Cécile; Lewis, David A; Puerta, Teresa; Keše, Darja; et al. (Microbial genomics, 2021)
Lymphogranuloma venereum (LGV), the invasive infection of the sexually transmissible infection (STI) Chlamydia trachomatis, is caused by strains from the LGV biovar, most commonly represented by ompA-genotypes L2b and L2. We investigated the diversity in LGV samples across an international collection over seven years using typing and genome sequencing. LGV-positive samples (n=321) from eight countries collected between 2011 and 2017 (Spain n=97, Netherlands n=67, Switzerland n=64, Australia n=53, Sweden n=37, Hungary n=31, Czechia n=30, Slovenia n=10) were genotyped for pmpH and ompA variants. All were found to contain the 9 bp insertion in the pmpH gene, previously associated with ompA-genotype L2b. However, analysis of the ompA gene shows ompA-genotype L2b (n=83), ompA-genotype L2 (n=180) and several variants of these (n=52; 12 variant types), as well as other/mixed ompA-genotypes (n=6). To elucidate the genomic diversity, whole genome sequencing (WGS) was performed from selected samples using SureSelect target enrichment, resulting in 42 genomes, covering a diversity of ompA-genotypes and representing most of the countries sampled. A phylogeny of these data clearly shows that these ompA-genotypes derive from an ompA-genotype L2b ancestor, carrying up to eight SNPs per isolate. SNPs within ompA are overrepresented among genomic changes in these samples, each of which results in an amino acid change in the variable domains of OmpA (major outer membrane protein, MOMP). A reversion to ompA-genotype L2 with the L2b genomic backbone is commonly seen. The wide diversity of ompA-genotypes found in these recent LGV samples indicates that this gene is under immunological selection. Our results suggest that the ompA-genotype L2b genomic backbone is the dominant strain circulating and evolving particularly in men who have sex with men (MSM) populations.
Keywords: molekulární epidemiologie; sexuální a genderové menšiny; Genomics; Australia; lidé; Middle Aged; Adult; Base Sequence; lymphogranuloma venereum; Molecular Epidemiology; homosexualita mužská; sekvenční analýza; Sexually Transmitted Diseases; Evolution, Molecular; Evropa; Austrálie; Lymphogranuloma Venereum; Homosexuality, Male; Humans; molekulární evoluce; Genotype; Sequence Analysis; Bacterial Outer Membrane Proteins; genomika; fylogeneze; proteiny vnější bakteriální membrány; sexuálně přenosné nemoci; Sexual and Gender Minorities; lidé středního věku; mužské pohlaví; mladý dospělý; sekvenování celého genomu; Chlamydia trachomatis; Young Adult; genotyp; Male; Aged; Whole Genome Sequencing; Europe; Phylogeny; dospělí; sekvence nukleotidů; senioři